Scenario Logic and Probabilistic Management of Risk in Business and Engineering - Solojentsev, E. D.; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
In this volume the methodological aspects of the scenario logic and probabilistic (LP) non-success risk management are considered. The theoretical bases of scenario non-success risk LP-management in business and engineering are also stated. Methods and algorithms for the scenario risk LP-management in problems of classification, investment and effectiveness are described. Risk LP- models and results of numerical investigations for credit risks, risk of frauds, security portfolio risk, risk of quality, accuracy, and risk in multi-stage systems reliability are given. In addition, a rather large number of new problems of estimation, analysis and management of risk are considered. Software for risk problems based on LP-methods, LP-theory, and GIE are described too. Audience This volume is intended for experts and scientists in the area of the risk in business and engineering, in problems of classification, investment and effectiveness, and post-graduates in those subject areas.
Acronyms and general notations -- Management and Risk -- The Human Being and Risks -- Principles of Risk Management in Design -- Risk Management at Debugging Tests -- Risk Management in Operation on Basis of Monitoring -- Risk Management on Dangerous Plant -- Bases of Logic and Probabilistic Calculus -- Logic and Probabilistic Method and Risk -- Automated Structural and Logical Modelling -- Foundations of the Risk LP-Theogy with Groups of Incompatible Events -- The Risk LP-Theory with GIE in the Classification Problem -- Identification of Risk LP-Models with Groups of Incompatible Events -- Risk Analysis in Systems with GIE -- Software for Risk Analysis and Management -- Risk LP-Models in Business -- Logic and Probabilistic Theory of Security Portfolio Risk -- Risk LP-Models in Engineering -- Risk LP-Theory in Problems of Effectiveness -- Conclusion.
Keywords: Mathematical logic; Combinatorics; Economic theory; Economics; Economic Theory/Quantitative Economics/Mathematical Methods; Combinatorics; Mathematical Logic and Foundations; Electronic books